Sistem Ekonomi dan Fiskal Pada Masa Khulafaurrasyidin - Akbar, Aziz; Misbah, Ahmad; Arisandi, Yusuf (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2022)
At the beginning of the reign of the Prophet Muhammad, Rasulullah SAW implemented an economic system that was highly committed to ethics and norms and his attention to justice and equality of the people, all of which were based on the Koran. Every activity during the reign of the Prophet saw must include the concept of maslahat which leads to Islamic ukhuwah. After the death of Rasulullah SAW, the government was continued by the Rashidun Khulafaur, namely caliphs who were given instructions and elected as heads of state and government as well as leaders of the Muslim community. In this article, we will explain how the Rashidun Khulafaur implemented an economic system during their respective reigns, namely the economic system under Abu Bakar Ash-Shiddiq, Umar bin Khatab, Uthman bin Affan, and Ali bin Abi Talib.